PENERAPAN DIAGRAM PARETO DAN DIAGRAM ISHIKAWA UNTUK MENGANALISA TINGKAT KECACATAN PRODUK LEMBARAN NATA DE COCO (Studi Di CV. AGRINDO SUPRAFOOD - YOGYAKARTA) - , SISCA DIANI ROSALINA; , Anggoro Cahyo Sukartiko, STP, MP, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Commanditaire Vennootschap (CV) Agrindo Suprafood is the food manufacturer company of nata de coco and supplier to the Corporation Limited (Co. Ltd.) such as Triteguh Manunggal Co.Ltd. and Sinar Mas Co.Ltd.. The defection of nata de coco slabs on harvesting stage can lead to the product markdown and detrimental to these company. The aims of final assignment report is identify the type of defection of nata de coco product, dominant factor which lead to defection, and cost loss which is caused by the defection as well as propose the alternative solution to minimize or even get rid of defection on nata de coco product. The data which is already gotten from the internship in CV. Agrindo Suprafood factory will be evaluated by using the Pareto Diagram which is kind of instrument to determine the type of defection that has significant impact and Ishikawa Diagram which is used to identify the correlation between the problems and possible causes. The defection type of nata de coco slabs which has been identified as follows (a) mildew that is dark brown till black spotting of nata de coco slabs, (b) kopyor that is the thickness of nata de coco slabs less than 0,5cm, and (c) boyor that is imperfect nata de coco slabs, it still being coconut water even though it has been aging up to seven days. This highest digression of nata de coco slabs that is the number of mildew nata de coco slabs are 251 samples (73%), the number of kopyor are 54 samples (16%), and the number of boyor are 37 samples (11%). The cost loss because of mildew as primary defection of nata de coco during three periods are 30.628 IDR (5,89%) for the first period, 36.504 IDR (7,02%) for second period, and the third period amount of 41.756 IDR (8,03%).